History, development, and the future impact of Egypt's soft power in Africa: broadcasting media approach - Mehany, Hany (AUC Knowledge Fountain, 2020)
The term "Soft Power" has been given a particular concern in the world of international relations. International broadcasting has been perceived by so many countries as one of the most effective tools that can produce and enhance a country's soft power. Today, Egypt seeks to enhance its leading role over the African continent through boosting its soft power resources and tools. Since the African Service in the Egyptian Directed Transnational Radio Network (EDTRN) and Nile TV International channel are the main Egyptian radio and TV services dedicated to enhance Egypt's soft power in Africa, this study aims to examine the experts' perception toward the soft power role of those two services. The study seeks also to explore the challenges and obstacles that may hinder the two services from working as effective soft power instruments for Egypt in Africa. This study advances a theoretical framework designed to help find a connection between soft power's resources, tools, and main goals from one side, and agenda setting and cultivation theories of mass communication on the other. The study used both quantitative and qualitative approaches in the data collection and analysis processes. The data analysis reflected glorifying the past effect, undermining the present influence, and doubting the future impact of the two services. The analysis also reflected confusion over implementing the strategic goals of the two services due to certain factors. The study found that the main challenges are represented in financial, technical, administrative difficulties as well as harsh competition with other international broadcasters. A set of recommendations were introduced to enhance Egypt's soft power in Africa through making better use of the African Service in the Egyptian Directed Transnational Radio Network and Nile TV International channel.